Efektivitas Undang-Undang Cipta Kerja Dalam Pembangunan Hukum Indonesia - Novanto, Arya Setya; Herawati, Ratna (JURNAL USM LAW REVIEW, 2022)
The purpose of this study is to determine the role of the rules governing the Job Creation Act which are effective in legal development in Indonesia. After the rules governing the Job Creation Law were passed, there were quite a lot of opposition given by people from various circles in Indonesia because they considered that many of the regulations contained therein were detrimental to some people and were made in a fairly fast time so that they created a negative impression in the community. In fact, the rules governing the Job Creation Law have a fairly good role in realizing effective legal development in Indonesia, therefore the author intends to raise this theme in order to find out the role of the rules governing the Job Creation Law in the development of effective Indonesian law. The urgency of this research is for the public to be able to see the phenomenon of the rules governing the Job Creation Act holistically, so that a positive side can be found from the formation of the rules governing the Job Creation Act. Furthermore, the research method that will be used in this research is the normative juridical research method. The novelty of this research lies in the analytical knife used, one of which refers to the theory of law and development from Mochtar Kusumaatmadja. The result of this research is that the rules governing the job creation law have effectiveness in the development of Indonesian law. Tujuan dari penelitian ini adalah untuk mengetahui peran aturan yang mengatur UU Cipta Kerja yang efektif dalam pembangunan hukum di Indonesia. Setelah aturan yang mengatur UU Cipta Kerja disahkan, cukup banyak pertentangan yang diberikan oleh masyarakat dari berbagai kalangan di Indonesia karena menganggap banyak regulasi yang termuat didalamnya merugikan sebagian masyarakat dan dibuat dengan waktu yang cukup cepat sehingga menimbulkan kesan negatif dimasyarakat. Sebetulnya aturan yang mengatur UU Cipta Kerja memiliki peran yang cukup baik dalam merealisasikan pembangunan hukum yang efektif di Indonesia, oleh sebab itu penulis bermaksud untuk mengangkat tema ini guna mengetahui peran aturan yang mengatur UU Cipta Kerja dalam pembangunan hukum Indonesia yang efektif. Urgensi penelitian ini adalah agar masyarakat mampu melihat fenomena aturan yang mengatur UU Cipta Kerja secara holistik, Sehingga dapat ditemukan sisi positif dari pembetukan aturan yang mengatur UU Cipta Kerja. Selanjutnya, metode peneltian yang akan digunakan pada penelitian ini adalah metode penelitian yuridis normatif. Kebaharuan pada penelitian ini terletak pada pisau analisis yang digunakan yang salah satunya merujuk pada teori hukum dan pembangunan dari Mochtar Kusumaatmadja. Hasil penelitian kali ini adalah aturan yang mengatur UU Cipta Kerja memiliki efektivitas dalam pembangunan hukum Indonesia. Kata kunci: Cipta Kerja; Efektivitas; Hukum; Pembangunan